Nilai Budaya dalam Novel Taira no Masakado Karya Eiji Yoshikawa (Kajian Antropologi Sastra) - Nauval Herlangga; Tia Ristiawati; Viana Meilani (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2021)
The purpose of this research is to describe the cultural values which are contained in Taira no Masakado novel. The author used descriptive analysis methods to analyse data. This research used literature study method, observe technique, and noting technique to collect data. Miles and Huberman descriptive analysis model was used to analyse data, which is an interactive analysis model. There are five aspects of cultural value orientation within society that was analysed using theory by Clyde Kluckhohn. Those values are, the aspect of human-life reality cultural value, which consists of the value of piety and religiousness. The aspect of human-nature reality cultural value, which consists of the natural resource usage and unity value. The aspect of interhuman cultural value, which consists of the responsibility, helping other, love, and friendship value. The aspect of human-work cultural value which consists of the patient, perseverance, hard work, and loyalty value. And The aspect of human-time cultural value, consists of the time usage value.